Implementasi Data Mining Untuk Mendukung Manajemen Perkerasan Jalan Di Kota Medan dengan Metode Intertasional Roughness Index - Siagian, Pardamean (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The use of road surface service level indicators with the International Roughness Index (IRI) has been widely used in various countries including Indonesia. Even the Pavement Management System in Indonesia was developed using IRI data. However, the breadth of the road network and the limitations of measuring instruments to assess road surface flatness have caused the recording of road service levels to be incomplete. However, the road network performance data that has been done manually has been widely used. The results of this complete data recording have been in the form of a database which is expected to be used to develop the IRI model through a data mining approach. The IRI model with data mining developed in this study uses an Artificial Neural Network and Support Vector Machines approach. The results of the development of this model can be used to utilize existing data to support the management of the road network with the Pavement Management System